HUBUNGAN HUKUM DENGAN KEKUASAAN DALAM PENGELOLAAN ZAKAT DI INDONESIA - Ahmad Faisal (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
The existence of amil as zakat collectors shows the need for the role of power in the management of zakat in Indonesia. Freedom to carry out religious obligations for its adherents in Indonesia does not necessarily release the government's responsibility in managing zakat so that the government then makes positive legal regulations related to zakat. In the perspective of legal philosophy, these rules must be obeyed because they are made by authorities that are coercive and contain sanctions if someone violates them. Starting from this, the author wants to see how the legal relationship with power in the management of zakat in Indonesia. This research is a normative juridical research that uses library materials as a source of study. Data obtained by collecting data through literature study. The positive zakat law made by the authorities in the management of zakat in Indonesia is useful for Muslims in carrying out their religious obligations so that the objectives of the zakat law sharia can be achieved. The law of zakat, which was originally a living law in the life of Indonesian society, is useful for the authorities or government in achieving the goals of their government. In essence, the legal principles of zakat originating from Allah SWT cannot be upheld without the power and authority to manage zakat without legal rules as well as a form of tyranny for the Indonesian people. In the management of zakat in Indonesia, the expected pattern of legal and power relations is that the ruler must comply with applicable laws and even be expected to complement each other in accordance with their respective functions so that the goals of power in Indonesia and law can be achieved, namely for human happiness.